Effect of selected Indian Medicinal Plants on PPARγ expression using 3T3 L1 Adipocytes as an In Vitro model (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: Azadirachta indica, Gymnema sylvestre, Momordica charantia, Syzygium cumini, and Trigonellafoenum-graecum are known for their antidiabetic effects; however, molecular mechanism/s have not been evaluated.We have attempted to elucidate a possible mechanism, namely, effect on peroxisome proliferator-activatedreceptor-g expression of these plant extracts using 3T3-L1 adipocytes. Materials and Methods: 3T3 L1 fibroblastswere initially differentiated into adipocytes, following which RNA was extracted and reverse transcribed to cDNAfor evaluation of PPARγ expression. Relative expression was normalized using GAPDH. Relative messengerRNA expression level was calculated according to ΔΔCT method and compared with Pioglitazone, a knowninsulin sensitizer. Results: M. charantia, S. cumini, and G. sylvestre showed an increase in PPARγ expression ascompared to Control cells. Pioglitazone also showed ~2.5-fold increase in PPARγ expression. Of these three plantextracts, hydroalcoholic extract of M. charantia showed maximum PPARγ expression with ~4.3-fold increasewhich was statistically significant compared to control and reference standards. Discussion: Activation of PPARγleads in improvement of insulin sensitivity through binding of synthetic drugs resulting in a decrease in insulin andglucose levels in patients with diabetes. Conclusion: Our data thus demonstrates that M. charantia, G. sylvestre,and S. cumini can be considered as PPAR modulators, acting through the PPAR signaling pathway resulting inenhanced transcription during adipocyte differentiation. This could be beneficial in the management of diabetesand its long-term complications with lesser toxicities.